Institutional levels of water management in the Colorado River basin region: A macro-historical geographic review - Wescoat, James L. (Frontiers in Water, 2023)
Complex water-stressed basins like the Colorado River in North America have multiple institutional levels of water management. Each institutional level is characterized by rules, organizations, and spatial jurisdictions that developed over decades to centuries to shape a dynamic multi-level system. After introducing the concept of institutional levels, and its relationship to geographic scales, this paper employs systematic bibliographic search methods to review their development in the Colorado River basin region. Results begin with the community level of water management from prehistoric Indian water cultures to early Hispanic water communities, 19th century water communities, and 20th century water organizations. Conflict among water communities shaped the state level of constitutional authority over water rights administration during the 19th century. Competition among states led in the 20th century to the interstate level of apportionment that often paralleled federal level water development policies, eventually leading to the international level of treaty relations between the U.S. and Mexico. This macro-historical geographic progression from institutions that are relatively small in size and early in time to those at higher levels offers insights into the institutional logic of complex water-stressed river basins like the Colorado River.